One‐Step Electrodeposition of NiCo2S4 Nanosheets on Patterned Platinum Electrodes for Non‐Enzymatic Glucose Sensing. Issue 12 (20th May 2016) - Kannan, Padmanathan Karthick; Hu, Chunxiao; Morgan, Hywel; Rout, Chandra Sekhar
Abstract: The preparation of NiCo2 S4 (NCS) nanosheets on photolithographically patterned platinum electrodes by electrodeposition was explored. The as‐prepared nanosheets were systematically characterized by field‐emission scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, and X‐ray photoelectron spectroscopy techniques. The NCS‐modified Pt electrode was used as a non‐enzymatic glucose sensor. The sensor response exhibited two linear regions in glucose concentration, with a limit of detection of 1.2 μm . The sensors showed that the as‐prepared NCS nanosheets have excellent electrocatalytic activity towards glucose with long stability, good reproducibility, and excellent anti‐interference properties, and thus, this material holds promise for the development of a practical glucose sensor. Abstract : The sixth sense : The non‐enzymatic glucose‐sensing properties of NiCO2 S4 nanosheets prepared by a one‐step electrodeposition method are studied. The sensor shows high sensitivity towards glucose with good stability. In addition, the sensor shows excellent anti‐interference properties in the presence of other sugars and possible interferent species.